2005
DOI: 10.1080/15502724.2004.10732007
|View full text |Cite
|
Sign up to set email alerts
|

Luminaire Dirt Depreciation for an Indirect Lighting System

Abstract: Sustainable design practices for lighting systems require that "just enough" luminaires are installed (and thus "just enough" electric power connected) to meet the visual and environmental needs of a space. Determining the proper quantity of luminaires requires estimating the expected light losses due to dirt accumulation. If the estimates employed in the lighting design process overstate the actual loss of light due to this accumulation, more luminaires will be specified than are actually needed, and thus mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Unlike lamp aging, that occurs under all conditions, the rate of lamp and luminaire soiling is site-specific. Levin and others Davis 2004) have found that fluorescent lighting equipment in modern offices does not become as dirty today as in previous eras when tobacco smoke and other pollutants degraded these systems. Similarly, UVGI luminaires in an up-scale conference room might easily last three years between cleanings whereas a busy, crowded hospital waiting room in a city center may require cleaning on a 3-6 month schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike lamp aging, that occurs under all conditions, the rate of lamp and luminaire soiling is site-specific. Levin and others Davis 2004) have found that fluorescent lighting equipment in modern offices does not become as dirty today as in previous eras when tobacco smoke and other pollutants degraded these systems. Similarly, UVGI luminaires in an up-scale conference room might easily last three years between cleanings whereas a busy, crowded hospital waiting room in a city center may require cleaning on a 3-6 month schedule.…”
Section: Discussionmentioning
confidence: 99%